Identificação de novos microrganismos com potencial probiótico e atividade contra enteropatógenos bacterianos - MENDES, Hermínio Benítez Rabello (2017)
The use of food for probiotic bacteria has recently been considered a possibility of prevention against the installation or attenuation of several infectious processes. Species belonging to the genera Bifidobacterium and Lactobacillus predominate in the gastrointestinal microbiota and are widely used in functional foods. In general, a selection of new probiotic strains for use in humans has as its source a human intestinal flora and breast milk. Thus, the objective of this study was to isolate and identify new species with potential probiotic from samples of breast milk and feces of infants exclusively breastfed, in addition to evaluating their probiotic potential. Samples of breast milk from two different lactation periods (colostrum and transitional milk) and samples of fecal material from infants were used. Isolation was used using MRSC and for Beerens for Lactic-Acid Bacteria and Bifidobacterium spp. respectively. Probiotic potential was assessed by physical pH and bile salt tolerance tests. Verified its ability to adhere to mucin and human intestinal cells (HT-29) and inhibit adhesion of different diarrheogenic strains of E. coli. The identification of the promising isolates was performed through the 16S rDNA region. Five isolates had acid-bile resistance, with CLM0109 insulation having 90.2% and 64.6% resistance, pH 3.0 and pH 2.0, respectively. These isolates have an ability to adhere to mucin and HT-29 cells, the isolate FEB0308 showed the highest level of adherence to HT-29 cells. The adhesion assay demonstrated that all isolates were absorbed by adhesion of diarrheogenic E. coli (DECs). Antimicrobial susceptibility analysis showed that 3 isolates showed resistance to one or two antibiotics (kanamycin and streptomycin). The molecular analysis allowed identifying the isolates as belonging to the species Lactobacillus casei. The results show that the five isolates present probiotic potential especially for use in the prevention and treatment of infections caused by DEC and demonstrate that milk and stool samples from infants can act as a source of potential probiotic bacteria.